Evaluation of Antioxidant Activity of Pulp and Seed Extracts from Garcinia cochinchinensis and Chemical Characterization of its Essential Oil - Kazmierczak, Elton; Bassani, André Victor; Contador, Maycon Hudson; Grzygorczyk, Sandra; Pessôa, Christiana Andrade; Magalhães, Cássia Gonçalves; Pereira, Romaiana Picada (Orbital: The Electronic Journal of Chemistry, 2025)
Garcinia cochinchinensis is native from Vietnam, used to cure allergy, itches and skin diseases. Considering the lack of studies about the chemical profile as well as the biological activities of G. cochinchinensis, this research aimed to evaluate antioxidant properties from its pulp and seeds extracts/fractions. Pulp was submitted to two different methods of extraction (liquid-liquid extraction with and without ultrasound extraction). Seed extracts were obtained with dichloromethane and ethyl acetate. Among these, the essential oil from the peel fruits of this species was analyzed by GC-MS. The antioxidant activity of extracts from pulp and seed was evaluated by the DPPH•, ABTS•+, FRAP, Iron (II) chelating methods, cyclic voltammetry and differential pulse voltammetry. Ethyl acetate in pH 8 and 4 fractions exhibited high values of phenolics and flavonoids content and showed effective antioxidant activity by the tested mechanisms. The essential oil from the peel is constituted by fatty esters and terpenes. Seed ethyl acetate extract exhibited expressive antioxidant activity in pH 6 via differential pulse voltammetry method. These promising fractions will be explored to isolate active phytochemicals and further the continuation of studies related to the evaluation of the antioxidant potential in vivo models.